Geographic disparities in lung transplant rates. Issue 5 (15th December 2018) - Kosztowski, Martin; Zhou, Sheng; Bush, Errol; Higgins, Robert S.; Segev, Dorry L.; Gentry, Sommer E.
Abstract : In November 2017, in response to a lawsuit from a New York City lung transplant candidate, an emergency change to the lung allocation policy eliminated the donation service area (DSA) as the first geographic tier of allocation. The lawsuit claimed that DSA borders are arbitrary and that allocation should be based on medical priority. We investigated whether deceased‐donor lung transplant (LT) rates differed substantially between DSAs in the United States before the policy change. We estimated LT rates per active person‐year using multilevel Poisson regression and empirical Bayes methods. We found that the median incidence rate ratio (MIRR) of transplant rates between DSAs was 2.05, meaning a candidate could be expected to double their LT rate by changing their DSA. This can be compared directly to a 1.54‐fold increase in LT rate that we found associated with an increase in lung allocation score (LAS) category from 38‐42 to 42‐50. Changing a candidate's DSA would have had a greater impact on the candidate's LT rate than changing LAS categories from 38‐42 to 42‐50. In summary, we found that the DSA of listing was a major determinant of LT rate for candidates across the country before the emergency lung allocation change. Abstract : This national study of the previous lung allocation policy, where the donation service area was the first unit of allocation, shows that, for some patients, listing location had a greater impact on their lung transplant rate than their lung allocation score.